Tuning Optical Nonlinearity of Laser-Ablation-Synthesized Silicon Nanoparticles via Doping Concentration. (3rd March 2014) - Chen, Lianwei; Jiang, Xiao-fang; Guo, Ziming; Zhu, Hai; Kao, Tsung-Sheng; Xu, Qing-hua; Ho, Ghim Wei; Hong, Minghui
Abstract : Silicon nanoparticles at different doping concentrations are investigated for tuning their optical nonlinear performance. The silicon nanoparticles are synthesized from doped silicon wafers by pulsed laser ablation. Their dispersions in water are studied for both nonlinear absorption and nonlinear refraction properties. It is found that the optical nonlinear performance can be modified by the doping concentration. Nanoparticles at a higher doping concentration exhibit better saturable absorption performance for femtosecond laser pulse, which is ascribed to the free carrier absorption mechanism.